Enantioselective separation and pharmacokinetic dissipation of cyflumetofen in field soil by ultra‐performance convergence chromatography with tandem mass spectrometry. Issue 7 (11th March 2016) - Liu, Na; Dong, Fengshou; Xu, Jun; Liu, Xingang; Chen, Zenglong; Pan, Xinglu; Chen, Xixi; Zheng, Yongquan
Abstract : Little data on the enantioselective separation of cyflumetofen exists, despite the fact that such data are essential to the assessment of the fate and potential toxic effects of cyflumetofen enantiomers. To address this issue, a simple and sensitive method for the enantioselective determination of cyflumetofen enantiomers in soil has been established using ultra performance convergence chromatography tandem triple quadrupole mass spectrometry. The effects of the chiral stationary phases, mobile phase, auto backpressure regulator pressure, column temperature, flow rate of the mobile phase, and compensation pump solvent were evaluated. The proposed method was applied to the study of the pharmacokinetic dissipation of cyflumetofen stereoisomers in soil under greenhouse conditions. The estimated half‐life of cyflumetofen isomers ranged from 12.2 to 13.6 days, and statistically significant enantioselective degradation was observed. This study not only demonstrates that there is an efficient and sensitive method for cyflumetofen enantioseparation, but also provides the first experimental evidence of the pharmacokinetic dissipation of cyflumetofen stereoisomers in the environment.